Vegetable Grafting: Principles and Practices 2017
DOI: 10.1079/9781780648972.0132
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular mechanisms underlying graft compatibility.

Abstract: Wild cardoon 'Sardo' Resistance to Verticillium High compatibility Trinchera et al. (2013) Artichoke 'Romolo' Cultivated cardoon 'Belgio' Resistance to Verticillium Moderate compatibility Trinchera et al. (2013) Artichoke 'Istar' Cultivated cardoon 'Bianco avorio' Resistance to Verticillium High compatibility Temperini et al. (2013) Artichoke 'Istar' Wild cardoon 'Sardo' Resistance to Verticillium Low compatibility Temperini et al. (2013) Pepper ' Adige' Pepper (Capsicum annuum) 'Serrano' Salt and drought resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 78 publications
1
64
0
3
Order By: Relevance
“…In addition, the presence of values out of the range of the parents suggest the influence of genetic background on the expression of these polygenic traits, which are potentially inherited from a grandparent (parent of a parent). It should be taken into account that the transmission of graft incompatibility is important for optimizing configuration crosses and improving efficiency of both scion and rootstock breeding programs [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the presence of values out of the range of the parents suggest the influence of genetic background on the expression of these polygenic traits, which are potentially inherited from a grandparent (parent of a parent). It should be taken into account that the transmission of graft incompatibility is important for optimizing configuration crosses and improving efficiency of both scion and rootstock breeding programs [6].…”
Section: Resultsmentioning
confidence: 99%
“…It may take several years to manifest failure with establishing graft-union that leads to major economic losses to growers and nurseries. In addition, the significant delay in the appearance of incompatibility symptoms renders the evaluation and transfer of new fruit tree genotypes to industry time-consuming, expensive and laborious [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in heterografted grapevine, transcripts associated with stress and defense responses are also accumulated. The cells at the graft interface are capable of detecting the presence of the non-self grafting partner, which may induce an immune-type response (Cookson andOllat, 2013 Cookson et al, 2014 ; ). However, some studies revealed that plant grafting induced phenotypic variation in anatomy and morphology ( ; Wang et al, 2017Reig et al, 2018.…”
Section: Cosgrove 2005mentioning
confidence: 99%
“…To the best of our knowledge, the most promising studies of the re-establishment of vascular tissues have studied the e ects of phenolic ff compounds ( ; ). More speci cally, Canas et al, 2015Pina et al, 2017 fi several studies have indicated that phenolic compounds are involved in ligni cation. Such compounds are important to the early growth stages fi of connections between scion rootstock combinations, as the cell walls of xylem tissues are dynamic structures composed of polysaccharides, phenolic compounds (for example, lignins), minerals, and proteins (Liu, 2012Herrero et al, 2014 ).…”
Section: Phenolic Compounds In Grafted Plant Vascular Connectionsmentioning
confidence: 99%